A Retrospective Study on How Psychopathic Traits Differentiate Recidivists From First-Time Female Youth Offenders in Juvenile Detention Centers. Issue 4 (8th August 2018) - Pechorro, Pedro; Braga, Teresa; Kahn, Rachel E.; Gonçalves, Rui Abrunhosa; Delisi, Matt
ABSTRACT: The aim of the present study was to analyze the relation between recidivism and self-reported psychopathic traits, more specifically the callous-unemotional, impulsivity, and narcissism dimensions of the psychopathy construct among female juvenile delinquents. The Antisocial Process Screening Device–Self-Report (APSD-SR) and other self-report psychometric instruments (i.e., Inventory of Callous-Unemotional Traits [ICU], Barratt Impulsiveness Scale, version 11 [BIS-11], Narcissistic Personality Inventory-13 [NPI-13]) independently measuring the different dimensions of psychopathy were completed by a sample of incarcerated female juvenile offenders (N = 81) that were retrospectively classified as first-time offenders versus recidivists. The only statistically significant relation between recidivism and psychopathic traits found was with narcissism, namely with the Grandiose/Exhibitionism and the Entitlement/Exploitativeness dimensions of the NPI-13. Our results argue for some utility of self-reported psychopathic traits in retrospectively predicting recidivism among female juvenile delinquents.